EIF Private Equity Mid-Market Survey 2024: Market sentiment - Antonia Botsari; Frank Lang (European Investment Fund (EIF), 2024)
Based on responses from 226 European private equity fund managers, the 2024 EIF PE Mid-Market Survey (the largest of its kind in Europe; conducted during July-August 2024) provides insights on the latest trends and developments in the European PE market. Key findings: Despite a still challenging market environment, the developments of the past two years reflect a normalisation away from the crisis mode seen in 2022, when PE Mid-Market fund managers' key concerns had been geopolitical uncertainty and market volatility. Fundraising and geopolitical uncertainty remain the two biggest challenges for the PE Mid-Market business, followed by portfolio company performance and the exit environment. General difficulties in finding potential buyers and a thin M&A market are mentioned as key challenges for exits. Approximately 2 in 5 PE Mid-Market fund managers state that the scale-up financing conditions have worsened in the last year. Recruiting high-quality professionals, the costs of production and labour and geopolitical uncertainty (and related consequences) have remained the three most important challenges for PE Mid-Market portfolio companies. PE Mid-Market fund managers report, on balance, a higher number of incoming investment proposals as well as of new investments undertaken. Respondents see promising investment opportunities in several sectors, particularly in the areas of Healthcare, ICT and the transition to greener and more efficient energy sources. With regard to respondents' expectations for future developments, for many market sentiment indicators the level of optimism expressed for the next 12 months has almost recovered to or even surpassed that observed in 2021- which was a record year for the PE/VC markets in Europe. Background: The EIF Equity Survey (combined EIF VC Survey and EIF Private Equity Mid-Market Survey) is the largest regular survey among General Partners across Europe, with a total of 624 respondents (398 VC, 226 PE). It feeds into our flagship publications delivering unique market insights on an annual basis. This publication is based on the results of the EIF PE Mid-Market Survey 2024. The study focuses on market sentiment and looks at the current situation, developments in the recent past as well as fund managers' expectations for the future
Keywords: 330